Deposition of 13C tracer and impurity elements on the divertor of Wendelstein 7-X. (14th September 2021) - Vuoriheimo, Tomi; Hakola, Antti; Likonen, Jari; Brezinsek, Sebastijan; Dittmar, Timo; Mayer, Matej; Prakash Dhard, Chandra; Naujoks, Dirk; Tuomisto, Filip
Abstract: Carbon impurity transport and deposition were investigated in the Wendelstein 7-X stellarator by injecting isotopically labelled methane ( 13 CH4 ) into the edge plasma during the last plasma operations of its Operational Phase (OP) 1.2B experimental campaign. 13 C deposition was measured by secondary ion mass spectrometry (SIMS) on three upper divertor tiles located on the opposite side of the vessel to the 13 CH4 inlet. The highest 13 C inventories were found as stripe-like patterns on both sides of the different strike lines. These high deposition areas were also analysed for their impurity contents and the depth profiles of the main elements in the layers. Layered deposition of different impurity elements such as Cr, Ni, Mo and B was found to reflect various events such as high metallic impurities during the OP1.2A and three boronizations carried out during OP1.2B.